2017
DOI: 10.1038/srep42176
|View full text |Cite
|
Sign up to set email alerts
|

Bigelovin triggered apoptosis in colorectal cancer in vitro and in vivo via upregulating death receptor 5 and reactive oxidative species

Abstract: Colorectal cancer (CRC) is the third most prevalent cancer and the third highest cancer-related mortality in the United States. Bigelovin, a sesquiterpene lactone isolated from Inula helianthus aquatica, has been proven to induce apoptosis and exhibit anti-inflammatory and anti-angiogenic activities. However, the effects of bigelovin on CRC and underlying mechanisms have not been explored. The present study demonstrated that bigelovin exhibited potent anti-tumor activities against CRC in vitro and in vivo. Big… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 50 publications
(67 reference statements)
1
34
0
Order By: Relevance
“…One could be based on sesquiterpene ability to increase oxidative stress in cancer cells (2). For example, bigelovin, a sesquiterpene lactone isolated from Inula helianthus aquatica, has been (9). Treatment of bladder cancer T24 cells with costunolide resulted in a dose-dependent inhibition of cell viability and induction of apoptosis, which was associated with ROS generation (10).…”
Section: Resultsmentioning
confidence: 99%
“…One could be based on sesquiterpene ability to increase oxidative stress in cancer cells (2). For example, bigelovin, a sesquiterpene lactone isolated from Inula helianthus aquatica, has been (9). Treatment of bladder cancer T24 cells with costunolide resulted in a dose-dependent inhibition of cell viability and induction of apoptosis, which was associated with ROS generation (10).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, in vivo experiments with animal models might be optimized based on in vitro data. Information from in vitro and in vivo studies will, in turn, facilitate and improve further clinical trials [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of this sesquiterpene lactone naturally produced by Inula helianthus aquatic on HT-29 and HCT 116 colorectal cancer cell lines was studied in a recent work by Li et al [ 49 ]. The authors found a marked antiproliferative effect caused by apoptosis induction.…”
Section: In Vitro Cell Line Modelsmentioning
confidence: 99%
“…Previously, several studies reported that natural compounds such as ginsenoside compound K and bigelovin induced DR5 to activate the extrinsic apoptosis pathway in colon cancer cell lines. 22,23 Our research group also reported that the methanol extract of Smilax china L. or b-phenylethyl isothiocyanate induced the DR5/caspase-8/Bid axis by regulating the extracellular signal-regulated kinase (ERK) or p38 MAPK signaling pathway, leading to caspase-mediated apoptosis in oral or cervical cancer cells. [24][25][26][27] These previous findings fully support DR5 regulation by natural products during apoptotic cell death pathways in cancer.…”
Section: Discussionmentioning
confidence: 96%